Current controversies in the management of Warthin tumour. Issue 999 (24th February 2009) - Thangarajah, T; Reddy, V M; Castellanos-Arango, F; Panarese, A
Abstract : Warthin tumour is the second most common benign neoplasm of the parotid gland. It has a low rate of growth and exhibits malignant transformation in 0.3% of cases. Although its aggressiveness has not been a concern, surgical resection remains the most common treatment modality. This entails the risk of a general anaesthetic and those pertaining to the procedure itself, most notably permanent facial nerve damage. This has led some authors to use conservative management, albeit rarely. There are those who condemn such a policy despite the encouraging results reported thus far. To understand the rationale underpinning non-operative management, it is imperative that one has a comprehensive understanding of the pathogenesis, clinical presentation and diagnosis of Warthin tumour. The aim of this review therefore is to detail these elements and clarify the current controversies in managing this lesion.